Exact and fast numerical algorithms for the stochastic wave equation - Andreas Martin; Sergej M. Prigarin; Gerhard Winkler (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2003)
On the basis of integral representations we propose fast numerical methods to solve the Cauchy problem for the stochastic wave equation without boundaries and with the Dirichlet boundary conditions. The algorithms are exact in a probabilistic sense.
urn:nbn:de:bvb:19-epub-1725-2
Keywords: 519